2005
DOI: 10.1177/19367244052200205
|View full text |Cite
|
Sign up to set email alerts
|

Flower Power: Assessing the Impact of the Magnolia Project on Reducing Poor Birth Outcomes in an At-Risk Neighborhood

Abstract: The past decade has seen tremendous improvements in the health status of children in the United States. In 1992, the infant mortality rate in the United States was at 8.5 per 1,000 live births. By 2002 that figure had declined to 6.9. However, the infant mortality rate for Jacksonville/Duval County in Northeast Florida has consistently remained higher than both the national and state rates, particularly for minority populations. The Magnolia Project was developed by a consortium of local health care providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Initially, health literacy focused upon reading and numeracy skills [42–45] then shifted to functional health literacy [37]; the shift was critical for serving women with low educational levels [3236]. Smith and Moore [4] found that women were able increase their MHL despite perinatal depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, health literacy focused upon reading and numeracy skills [42–45] then shifted to functional health literacy [37]; the shift was critical for serving women with low educational levels [3236]. Smith and Moore [4] found that women were able increase their MHL despite perinatal depression.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal Health Literacy (MHL) meant women employed cognitive and social skills based in experience to access, understand and evaluate information to promote health for themselves and their children [ 37 41 ]. Initially, health literacy focused upon reading and numeracy skills [ 42 – 45 ] then shifted to functional health literacy [ 37 ]; the shift was critical for serving women with low educational levels [ 32 36 ]. Smith and Moore [ 4 ] found that women were able increase their MHL despite perinatal depression.…”
Section: Introductionmentioning
confidence: 99%